Paper Retracted - EVALUATION OF CHILDREN GROWTH PARAMETERS – A MULTIDISCIPLINARY ISSUE - Carmen Vulpoi; Doina Azoicăi; Maria-Christina Ungureanu; Mihaela Cristina Anton; Raluca Kert; Ioana Armaşu; Iuliana Vulpoi-Naghel; Cristina Preda (European Scientific Journal, ESJ, 2015)
Growth is a complex process; starting in utero and continuing until the end of puberty. Being a marker of children health, growth evaluation is an important tool. A positive secular trend of height was noticed in the last century. On the other side, geographical differences in height have been noticed, suggesting the necessity of local growth charts. We evaluated growth parameters in the Eastern part of Romania. Study group included 1,949 children (987 girls and 962 boys) aged between 7-16 years, living in the same city, with no chronic illness. The evaluation was performed with the help of the school authorities, and parents’ consent. Anthropometrical parameters (height, weight, and puberty stage) were recorded. Results were compared to the last Romanian growth charts, dating from 1971, and the European Prader standards, from 1989. Mean differences were +5.3 cm in boys and +5.9 cm in girls vs. Romanian charts, and +4.3 cm in boys and +3.6 in girls vs. Prader charts, higher at 10-11 years, probably correlated with earlier puberty onset. Weight had the same tendency of growing in boys (+1.43 kg) and in pre-pubertal girls (+1.1 kg), but after 11 years, girls’ weight was lower, is probably correlated with the more or less anorectic beauty ideal of nowadays. There is a significant increment of height in both boys and girls, suggesting the necessity of new, actualized standards. Assessing children health can be done only with an interdisciplinary team, medical and non-medical.